Cardiac surgery: moving away from intensive care. Issue 10 (October 1992) - Chong, Jin Long; Pillai, Ravi; Fisher, Anthony; Grebenik, Catherine; Sinclair, Michael; Westaby, Stephen
Abstract : Objective —To evaluate outcome in patients managed outside an intensive care unit after open heart surgery. Background —The high cost of cardiac surgery is mainly due to the needs of traditional postoperative care. The requirements for intensive care and treatment has decreased with improvements in techniques of cardiac surgery and anaesthesia. In this setting the need to continue to depend on intensive care units for the recovery of cardiac surgical patients is questionable on clinical and economic grounds. Design —Postoperative outcome in 245 patients over a four month period was studied prospectively. Patients —Mean age of the patients was 63·2 years. They underwent a wide variety of operative procedures. Ninety percent of them recovered in a dedicated three bed cardiac surgical recovery area where the management protocol led to rapid extubation and step down in dependency care. Results —Median time for ventilatory support was 90 minutes after transfer to the area. Only five patients were subsequently admitted to the general intensive care unit for prolonged respiratory and cardiac support. Ten patients were electively admitted to the general intensive care unit. Two deaths occurred in hospital in this group (0·8%). Four patients were ventilated for 24 hours in the recovery area itself and made an uncomplicated recovery. Conclusion —This study confirms that over 90% of patients undergoing cardiac surgery would recover safely and be treated effectively in a more economical area than intensive care.